Forestry and Climate Change - Freer-Smith, Peter H (CABI, 2014)
I would like to thank all those who travelled to Wilton Park to work on forestry and climate change. This really was a working conference, where many participants gave presentations, chaired workshops and assisted in reporting. The conference was organized by Forest Research, the Forestry Commission’s research agency, on whom we depend so much, not only for scientific research but also for advice at all levels. Peter Freer-Smith, Mark Broadmeadow and Jim Lynch took the lead in organizing the meeting and in the production of the book inspired by this conference. I would also like to thank OECD for co-sponsoring the conference. In the UK the subject of climate change was often headline news during 2006 and recently Sir Nicholas Stern’s report The Economics of Climate Change (The Stern Report) has been published. Commissioned by the UK Government, this report highlighted an urgent need for action. Thus the timing for an OECD Conference on Climate Change and Forestry could not have been better. Climate change is a concern to governments and international organizations across the world, and this conference helped us to identify the part that forestry can play in addressing this important global concern